Genetic, cytological and molecular characterization of chia (Salvia hispanica L.) provenances. (August 2017) - Palma-Rojas, Claudio; Gonzalez, Carla; Carrasco, Basilio; Silva, Herman; Silva-Robledo, Herman
Abstract: Chia ( Salvia hispanica L.) is a native plant to southern Mexico and northern Guatemala although in these days also is cultivated in others South American countries such as Bolivia and Argentina. This study describes a genetic, cytological and molecular characterization of nine provenances of Salvia hispanica . The genome size was estimated to be C = 0.84 pg of DNA. Also a quantitative description of the karyotype is presented. The karyo-idiogram analysis shows that pairs 5 and 6 of the chromosomes are in the limit between submetacentric and subtelocentric types. When the nine provenances were studied using ISSR markers we were able to observe a very low genetic variability for the ISSR loci analysed (h = 0.08–0.15; I = 0.10–0.23; P = 9.3–23.5%). Selfing and reduced genetic background produced by genetic drift and human selection, might explain in part the scarce genetic differentiation found among provenances. These genetic characterizations are part of the basic genetic information, which should be considered for improvement and germplasm conservation programs. Highlights: The chromosome number for chia ( Salvia hispanica L.) is 2n = 2x = 12. The genome size for S. hispanica was estimated as C = 0.84 pg DNA. When nine provenances of chia were studied using ISSR markers, a very low genetic variability for the ISSR loci analyzed was observed.